LITERATURE REVIEW; TRANSFORMASI PENGGUNAAN HURUF DAN TANDA BACA DI ERA DIGITAL PERSPEKTIF PENDIDIKAN BAHASA INDONESIA - Fajar, Adam Hafidz Al; Dzikri, Muhammad Aksari; A'yun, Hanifa Qurota (Universitas Peradaban, 2025)
This study aims to explore the transformation of letter and punctuation usage in the digital age, with a focus on the impact of social media on formal writing. Employing a qualitative method through literature review, the research analyzes various relevant sources to identify changes in writing habits resulting from digital communication. The findings reveal that while social media offers convenience and speed in communication, informal writing habits—such as neglecting capitalization, using abbreviations, and improper punctuation—can undermine the quality of formal writing among the younger generation. This presents a challenge for the language education system, which must adapt to these changes without neglecting the importance of teaching correct writing fundamentals. Therefore, it is crucial for educational institutions to teach the distinction between informal social media writing and the formal writing required in academic and professional contexts. The study provides recommendations for educators to integrate an understanding of language changes with writing instruction to ensure that students continue to maintain high writing standards amid rapid technological advancement. Keywords: Transformation of Letters and Punctuation, Social Media, and Language Education